Study of initiation and development of short vacuum gaps pulse breakdown in nanosecond range; Pt. 1; Proceedings of the IIIrd International Symposium on Discharges and Electrical Insulation in Vacuum, Paris, 1968 - Mesyats G. A. Gennady Andreyevich; Bugaev S. P.; Proskourovsky D. I.; Eshkenazy V. I.; Urike Ya. Ya. (1968, 1968)
В фонде НТБ ТПУ отсутствует